2003
DOI: 10.5483/bmbrep.2003.36.5.462
|View full text |Cite
|
Sign up to set email alerts
|

Use of RAPD Fingerprinting for Discriminating Two Populations of Hilsa shad (Tenualosa ilisha Ham.) from Inland Rivers of Bangladesh

Abstract: The Random Amplified Polymorphic DNA-Polymerase Chain Reaction (RAPD-PCR) was applied to analyze the genetic variation of the Hilsa shad, Tenualosa ilisha Ham., from the two major inland rivers (Padma and Meghna) in Bangladesh. Twenty-eight random 10-mer primers were primarily scored in 8 individuals from each of the two locations. Fifteen primers, which gave polymorphism, were selected and used in the final analysis of 34 individuals from the two sites. Using these primers, 480 scorable DNA fragments were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
1
9
1
Order By: Relevance
“…However, this conclusion may be contradicted through the presence of some private haplotypes in the Balashi and Chandpur populations. These results also run counter to those of Shifat et al (2003), who reported that the two river populations of T. ilisha , the Meghna and the Padma were different stocks, though they observed certain alleles shared by some individuals of these two river samples. The presence of private haplotypes indicates the extent of mixing between populations.…”
Section: Discussioncontrasting
confidence: 99%
“…However, this conclusion may be contradicted through the presence of some private haplotypes in the Balashi and Chandpur populations. These results also run counter to those of Shifat et al (2003), who reported that the two river populations of T. ilisha , the Meghna and the Padma were different stocks, though they observed certain alleles shared by some individuals of these two river samples. The presence of private haplotypes indicates the extent of mixing between populations.…”
Section: Discussioncontrasting
confidence: 99%
“…The lack of genetic structure in the neutral loci indicates that all Hilsa shad individuals from different collection sites are connected via high levels of gene flow between the marine water and freshwater environments, which is consistent with previous studies using allozyme [14,15], restriction fragment length polymorphism (RFLP) [16,17], random amplification of polymorphic DNA (RAPD) markers [54][55][56][57], and mitochondrial DNA cytochrome b gene nucleotide sequencing [18,19]. The genetic divergence depicted by the outlier loci dataset suggests that dispersion may likely happen in the foraging ground in marine and brackish water habitats, allowing for a substantial gene flow among distant locations.…”
Section: Discussionsupporting
confidence: 90%
“…12), OPH-13 gave 9 fragments from150 to 680 bp (Table 14 & Fig. 13), (same primer OPH-13 gave 48 bands, 9 of them polymorphic in Tenualosa ilisha Ham of the Clupeidae family (Shifat et al, 2003), OPM-11 gave 13 fragments in the four species of Cephalopholis ranged in size between 120 and 580 bp (Table 15 & Fig. 14) and primer OPM-12 generated 10 fragments from150 to 600 bp (Table 16 & Fig.…”
Section: Resultsmentioning
confidence: 95%